PERFORMING PARENTAL RIGHTS DE LEGE LATA, DE LEGE FERENDA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
A number of surveys over the past couple of decades have shown thatdivorce has negative consequences on children. This is a challenge tostudy the model of parental responsibility after a divorce that correspondsto the principle of respecting the best interests of the child. In the paper,the authors make a comparative analysis of the exercise of the parentalrights after the divorce de lege lata. The authors analyze the consequencesof divorce on children, as well as the results of sociological research onthe impact of the joint exercise of parental rights after divorce on children,which is a modern tendency in the world in recent years. This research isdone in order to propose the best solutions that would be implemented inMacedonian legislation de lege ferenda. The authors believe that reformsof the Macedonian family legislation regarding the exercise of the parentalright after the divorce are urgently needed, given the fact that the numberof divorces in Macedonia is constantly on the rise, and our legislation hasan extremely outdated conception of parenting after divorce, leading toserious problems for children and parents after the divorce.